Non-contrast MRI Surveillance of Craniopharyngiomas using a balanced steady state free precession (bSSFP) sequence - Trinh, Kelly; Tang, Michael; White-Dzuro, Claire; Lang, Min; Buch, Karen; Rincon, Sandra (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: Contrast-enhanced MRI (CEMRI) is a commonly used imaging modality for craniopharyngioma surveillance; however, it carries risks such as allergic reaction and gadolinium deposition. This study evaluates the efficacy of non-contrast enhanced MRI (NCMRI) with a balanced steady state free precession (bSSFP) sequence compared with CEMRI T1-weighted imaging for craniopharyngioma surveillance.MATERIALS AND METHODS: 29 craniopharyngioma patients (16 female/13 male, mean age=21.5± 4.3 years) with CEMRIs including a bSSFP sequence were evaluated. For each patient, 2 blinded neuroradiologists compared the dimensions of residual craniopharyngioma on noncontrast and contrast-enhanced sequences. Tumor volume and solid/cystic component measurements were evaluated using paired t-tests. Diagnostic confidence levels for NC-and CE evaluations were measured using a 3-point scale (2=confident,1=adequate,0=unsure). Analyses of tumor involvement of cranial nerves and adjacent vasculature and diagnostic confidence were performed using Fisher’s exact and chi-square tests.RESULTS: No significant difference was observed between residual tumor volumes in both studies (18.86±21.67 cm3 vs 17.64±23.85 cm3, p=0.55) and measurements of dominant solid component volume, number of cystic components, and largest cystic component volume (2.71±3.47 cm3 vs 3.95±5.51 cm3, p=0.10; 2.5±1.5 vs 2.9±1.5, p=0.10; 7.61±13.41 vs 6.84±13.37 cm3, p=0.22, respectively). Tumoral involvement of cranial nerves II (p=0.64), III (p=0.42), and adjacent vasculature (p=0.05) showed no significant differences in detection. Diagnostic confidence was comparable evaluating cranial nerve II, vascular structures, and third ventricle (p>0.05) involvement. Higher levels of confidence were observed with bSSFP sequences for detection of cranial nerve III involvement (p=0.0001) and with ce-T1W for cavernous sinus involvement (p=0.02).CONCLUSIONS: NCMRI techniques using a bSSFP sequence provides similar characterization of craniopharyngiomas as contrast enhanced techniques.ABBREVIATIONS: 3D DRIVE, 3-dimensional driven equilibrium; ACA, anterior cerebral artery; bSSFP, balanced steady-state free precession; ce-T1W, contrast-enhanced T1-weighted imaging; CN, cranial nerve; GTR, gross total resection; STR, subtotal resection